2017
DOI: 10.1111/puar.12719
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Relating: Theory and Evidence on the Formation of Street‐Level Bureaucrats’ Workplace Networks

Abstract: Despite the importance of peers in forming role expectations, fostering group identity, and facilitating job learning, limited theory and empirical evidence exist on the antecedents of street-level peer relationships. To address this gap, the authors draw on social capital and social exchange theories to develop hypotheses about the micro-social foundations of street-level bureaucrats' peer selection. The hypotheses are tested using a rich data set from an intraorganizational network of teachers in a large urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 75 publications
1
33
0
Order By: Relevance
“…For that reason, the use of ERGM to test hypotheses on social relations within a network can be easily found in social sciences research. Public administration is no exception (e.g., Berardo and Lubell ; Feiock, Lee, and Park ; Ingold and Leifeld ; Nisar and Maroulis ). This study employs ERGM to estimate the effects of covariates on the ties in a network configuration while estimating parameters describing the forms of dependence (Cranmer and Desmarais ) that can exist in relational data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, the use of ERGM to test hypotheses on social relations within a network can be easily found in social sciences research. Public administration is no exception (e.g., Berardo and Lubell ; Feiock, Lee, and Park ; Ingold and Leifeld ; Nisar and Maroulis ). This study employs ERGM to estimate the effects of covariates on the ties in a network configuration while estimating parameters describing the forms of dependence (Cranmer and Desmarais ) that can exist in relational data.…”
Section: Methodsmentioning
confidence: 99%
“…In interpreting the ERGM results, conceptualization of an ERGM is useful as a logistic regression that predicts the existence of a tie between a pair of individuals (Nisar and Maroulis ). Thus, the prediction in an ERGM is a function of individual‐level, dyadic, and higher‐order structural variables, where “estimated coefficients indicate the correspondence between a one‐unit change in the predictor and the log odds of the tie existing” (Nisar and Maroulis , 833).…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of the articles published in prominent journals between 2003 and 2017, we found 278 articles on SLBs. The abstracts of these articles suggested that only five of them mobilized relational dimensions in the analysis (De Corte, Verschuere, & De Bie, ; Maroulis, ; Nisar & Maroulis, ; Siciliano, ; Siciliano, ). Additionally, these articles only consider social relationships among peers and neglect bureaucrat–citizen relations.…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…For example, there are material inducements, social incentives, and commitments that are created for a common purpose (Hirsch ). The literature has examined how existing relational ties are utilized in mobilization (Calhoun ; Oberschall ; Pinard ), and some literature has investigated on how emergent solidarity is generated in community groups (Feiock, Lee, and Park ; Musso and Weare ; Nisar and Maroulis ; Siciliano ; Siciliano et al ). The recognition of the solidarity‐formation process is linked to discussions of political homophily during collaboration.…”
Section: Political Solidarity Accounting For Political Homophilymentioning
confidence: 99%